Impact of Diastasis Recti Abdominis and Low Back Pain on Quality of Life in Post-Partum Female - Bhavna Gandhi1 , Shalaka Dhankar2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: The separation of the two rectus abdominis muscle along with linea alba is called diastasisrecti abdominis. Diastasis recti is comman in Post-partum females. In Post-partum period Low back Pain isvery comman which lead to daily activity limitation. Post-Partum women complaint regarding there usualactivities, mobility, pain, which affect the quality of life in individual.Aim: To study the” Impact of diastasis recti and low back pain on quality of life in post-partum females”Method: This study will be carried out in Physiotherapy OPD, Ravi Nair Physiotherapy College andAVBRH, Sawangi (Meghe), Wardha. Diastasis recti will be evaluated in Post-partum females. Impact ofDiastasis recti and Low back pain on Quality of Life in post-partum female. Low back pain is going to asseswith the help of Modified Owestry low back pain disability questionnaire .And quality of Life with the helpof Maternal postpartum questionnaireResults: Study yet to be commenced.Conclusion: Conclusion will be published after the result are analysed.